Effect of Recreational Activities in Schizophrenic Patients Rehabilitation in Promoting Social Skills - Masoud Fallahi-Khoshknab (Journal of Rehabilitation, 2006)
Objective: one of group interventions in rehabilitation of schizophrenic patients is recreational activities intervention, in this type of rehabilitation therapist participates patients in recreational activities and hobbies, which promotes activity of daily livings and social skills. Our purpose of this study was investigating the effectiveness of recreational interventions in schizophrenics’ social skills.